COMPUTER SELF EFFICACY (CSE) MAHASISWA AKUNTANSI DALAM PENGGUNAAN TEKNOLOGI INFORMASI: TINJAUAN BERDASARKAN GENDER - Carolina Carolina; MI. Mitha Dwi Restuti (Jurnal Akuntansi Bisnis, 2011)
The need ./or information can be accessed more easily if they are supported by information technology (IT). Now, almost all accounting activity is done wth computerized system. Accounting students prepared to become accountants with information technology ability. information technology only creates new opportunities for individuals who are reality qualified, because of the sophistication and the benefits of IT could be meaningless if the IT user did not develop in line with the development of IT. This study investigates whether there are Computer Self Efficacy (CSE) differences on accounting students by gender in the use of information technology. A bout 198 accounting students were used as samples. Reliability and validity tests performed in the test questionnaire. The analisis tools are independent i-test. The result were there are differences on Computer Self Efficacy (CSE) accounting students in the use of information technology by gender, which the CSE male is higher than CSE femal.